E.B. Dongala (1988). Jazz et vin de palme. París: Imprimérie Nouvelle, 156 pp. - Saganogo, Brahiman (Estudios de Asia y África, 2018)
E.B. Dongala (1988). Jazz et vin de palme. París: Imprimérie Nouvelle, 156 pp.